Secondary Metabolites of Various Indonesian Medicinal Plants as SARS-CoV-2 Inhibitors: In Silico Study - Tungary, Emilia; Wahjudi, Mariana; Kok, Tjie (Fakultas Farmasi, Universitas Surabaya, 2022)
Corona virus disease 2019 caused by SARS-CoV-2 infection emerged in late 2019 and still become a worldwide pandemic up to this point with the drug remain unavailable. Meanwhile, Indonesia has an abundance variety of medicinal plants that are potential to be developed as inhibitors. By using the key role proteins as drug targets, namely spike glycoprotein and RNA-dependent RNA polymerase (RdRp) of delta variant of SARS-CoV-2 (which is known as strongly transmitted and highly virulent), we can develop inhibitors for the target proteins from potential Indonesian medicinal plants to prevent the protein interactions for viral entry and proliferation that leading to organ disfunction and death. This study aimed to identify the secondary metabolites of various Indonesian medicinal plants as SARS-CoV-2 inhibitors. The 184 ligands from nine plants were collected from IJAH webserver and their SMILES notation were collected from PubChem. Meanwhile 3D structures of spike glycoprotein (PDB ID: 6VXX) and RdRp (PDB ID: 6M71) were obtained from protein data bank (PDB). Molecular docking was conducted between ligands and the two SARS-CoV-2 proteins using Autodock Vina in PyRx with hesperidin and remdesivir as control compounds. Several potential compounds were selected for drug-likeness analysis and toxicity analysis. Results showed that lantanolic acid has the same amino acid interaction with RdRp as the control compound. It formed a hydrogen bond with Ser784 and hydrophobic bonds with Tyr32 and Ser7709. It had lower binding affinity than the control compounds, eligible as oral drug, and had LD50 of 2589 mg/kg.